Network Science, Nonlinear Science and Infrastructure Systems - Friesz, Terry L.; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
Network Science, Nonlinear Science and Infrastructure Systems has been written by leading scholars in these areas. Its express purpose is to develop common theoretical underpinnings to better solve modern infrastructural problems. It is felt by many who work in these fields that many modern communication problems, ranging from transportation networks to telecommunications, Internet, supply chains, etc., are fundamentally infrastructure problems. Moreover, these infrastructure problems would benefit greatly from a confluence of theoretical and methodological work done with the areas of Network Science, Dynamical Systems and Nonlinear Science. This book is dedicated to the formulation of infrastructural tools that will better solve these types of infrastructural problems. .
A Revolution in Infrastructure Network Research and Engineering? -- Networks and Dynamics: The Structure of the World We Live In -- Modeling Large Scale and Complex Infrastructure Systems as Computable Games -- Dynamic Competition on Networks: Differential Variational Inequalities, Limited Warfare and Internet Vulnerability -- Characterization and Monitoring of Nonlinear Dynamics and Chaos in Manufacturing Enterprise Systems -- Evolutionary Traffic Flow Landscapes: A Fitness Approach for ITS Management -- Network Connectivity Models: An Overview and Empirical Applications -- An Application of Complex Network Theory to German Commuting Patterns -- Assessing Critical Components in Transportation Systems: Economic Models and Complex Network Science Approaches -- A Simulation-Based Dynamic Intermodal Network Equilibrium Algorithm -- Modeling the Transient Nature of Dynamic Pricing with Demand Learning in a Competitive Environment -- An Evolutionary Variational Inequality Formulation of Supply Chain Networks with Time-Varying Demands -- Some Amazing Properties of Road Traffic Network Equilibria.
Keywords: Mathematics; Operations research; Decision making; Computer communication systems; Dynamics; Ergodic theory; Game theory; Economic theory; Regional economics; Spatial economics; Mathematics; Game Theory, Economics, Social and Behav. Sciences; Dynamical Systems and Ergodic Theory; Computer Communication Networks; Operation Research/Decision Theory; Regional/Spatial Science; Economic Theory/Quantitative Economics/Mathematical Methods